Evaluation of sorghum in gluten-free soy sauce - Pearson, Cole (Kansas State University, 2017)
Gluten-free products are becoming more prevalent in the market today, however there are a few types of products that have “hidden” gluten and people will not realize until after consumption. Products like soy sauce and beer are sources of gluten that people don’t know about. Soy sauce contains wheat as a main ingredient so replacing it with a gluten-free flour such as sorghum may produce a product similar to wheat-based soy sauce. Sorghum was used in this experiment since it is a grain grown in the mid-western region of the United States and a growing food ingredient in the global market. Sorghum can come in many different varieties and colors so we used different varieties in this study. Four treatments were done using three different sorghum flours (black, white, and waxy sorghum flour) and a wheat flour for a control. Cooked soybeans were mashed in a kitchenaid mixer and the treatment flour was added to make a dough. That dough was formed into a log and cut into slices. The slices were then staked with wet paper towels to mold. After 13 days of molding, the slices that were made were dried, placed in a salt solution, and fermented for 100 days. The solution was mixed with a spatula for 30 seconds to homogenize the mixture every 2-3 days and samples were taken every 10 days to test for pH, salinity, and color. Once the 100 days were complete and the pH of each treatment did not drop for consecutive testing periods, the liquid was removed from the solids and pasteurized. The pH curve did show that a fermentation process did occur, however there was no control over what microorganism could grow. Consumer testing was not performed since all test sauces were deemed unacceptable at the initial screening.
Keywords: Gluten free; Soy sauce; Sorghum; Food ingredient; Fermentation; pH value